Shattered mirror [large type] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2018)
Eve Duncan receives a package containing a skull-- and instructions for Eve to do her work reconstructing it. When she does, a beautiful woman's face emerges. But when Eve is introduced to the dead woman's mirror image, a game is on where her twin's life hangs in the balance.